(untitled) (Journal of Health Sciences, 2016)
Influenza is one of the most common respiratory diseases in the world, annually causing over one million of deaths. It is triggered by one of the types of influenza viruses (A, B or C). Most usually, it assumes the form of epidemic disease, sometimes it is a pandemic, and is very rare as a sporadic disease. In temperate zones, the influenza occurs seasonally - during the cold months of a year. In tropics, however, it occurs throughout the year, though the highest number of patients is registered during the rainy seasons. Influenza is a mild disease for young and healthy persons; however, if affecting those with a weakened immune system, it can lead to complications and even to death. The only effective preventive measure is vaccination, which precludes the disease. So far, no consensus is reached on whether the vaccination should be compulsory or recommended and who should be vaccinated. In most European countries, vaccination is recommended for certain categories of the population, while the United States recommend it to the entire population above six months of age.